Analisis Pelanggaran Hukum Disiplin Finansial Standar Profesional Account Officer oleh Pegawai dalam Penyaluran Kredit di Bank BRI: Studi Putusan: No. 10/G/2013/PHI/PN.KPG - Shinta Adella; Agnes Fitryantica (Lembaga Pengembangan Kinerja Dosen, 2024)
Misconduct is an act that violates applicable legal provisions and contravenes professional norms. In the context of banking, violations of financial discipline and professional standards can have a serious impact on the financial stability and reputation of the institution. This research analyzes violations of financial discipline law committed by employees in lending at Bank BRI, based on a case study of Decision No. 10/G/2013/PHI/PN.KPG. These violations included non-compliance with lending procedures, abuse of authority, and violation of professional ethical standards set by the bank. This research uses a normative juridical approach, which focuses on the study of applicable legal norms through the analysis of legal documents and related literature. In its decision, the panel of judges considered evidence and witness testimony that showed negligence and non-compliance by the Account Officer. The implementation of sanctions for these violations is expected to provide a deterrent effect and improve compliance with financial discipline and professional standards. The study also identifies the steps taken by Bank BRI to improve its supervisory system and training for employees to prevent the recurrence of similar violations in the future. This study makes an important contribution to understanding the dynamics of financial discipline law violations in the banking sector and the remedial measures that need to be taken.